Un modelo interactivo en comprensión lectora. (1999)
This is a proposal on interactive model of meaning construction in reading comprehension . It is analized how the reader starts from a personal context (perception, inferential capability, memory, metacognitive strategies) and buildg meanings to produce a virtual text or a subjunctive reality when interacting with the text. When stressing the text and its context, the model specifies linguistic text units (words, sentences, speech) and meaning construction created by the author. Dealing with text or speech structure, the model presents two kinds of speech (literary and scientific) and two modalities of thought (narrative and pragmatic). In short, the model shows the way the reader not only captures the contents of the text but also how she/he generates a creative construction when interacting with it. To verify the model it is suggested to focus on the interaction text-reader taking into account the context of each one, and to use the narrative text.